La enseñanza de la expresión escrita en el método comunicativo mediante el enfoque al proceso - Madrigal Abarca, Marta (2012)
The objective of this article is to show how the activities that are realized in the prewriting stages (draft and revision of the process focus) can be integrated into the Communicative Method to bring the writing exercise to a more efficient conclusion. This method, upon integrating the four skills, will permit multiple disciplines and room for the teaching of the written expression that will be more dynamic and interesting for the students. This is because they will understand that the purpose is in the communication and the development steps taken to achieve that communication and not so much in the final product.